Kinetic energy management in road traffic injury prevention: a call for action - Khorasani-Zavareh, Davoud (J Inj Violence Res, 2015)
By virtue of their variability, mass and speed have important roles in transferring energies during a crash incidence (kinetic energy). The sum of kinetic energy is important in determining an injury severity and that is equal to one half of the vehicle mass multiplied by the square of the vehicle speed. To meet the Vision Zero policy (a traffic safety policy) prevention activities should be focused on vehicle speed management. Understanding the role of kinetic energy will help to develop measures to reduce the generation, distribution, and effects of this energy during a road traffic crash. Road traffic injury preventive activities necessitate Kinetic energy management to improve road user safety.